DEVELOPMENT OF A MATHEMATICAL MODEL FOR CREEP OF CONCRETE WITH REFERENCE TO BAGHDAD CLIMATE - Riyadh S. Al-Rawi; Zainab M. I. Kammouna (Journal of Engineering, 2003)
the present investigation is concerned with thesevaluation of creep behavior of concrete under variable temperature and relative humidity. It includes analytical and experimental parts. In the analytical part, BP-KX creep model is presented. As this model  considers temperature and relative humidity to be constant, it was modified through considering them to be variable with time, which is the usual case. Functions for the daily variation of these two parameters, according to Baghdad climate, were developed and substituted in the model. In the experimental part, three series of cylindrical specimens (100mm x 200mm) were prepared for the creep test. In series (1), the temperature was raised and simultaneously the relative humidity was lowered just after loading. Series (2). specimens were loaded at high temperature and low relative humidity followed by low temperature and high relative humidity. Series (3) specimens were loaded at low temperature ard high relative humidity followed by high temperature and low relative humidity.Comparison between the analytical and the experimental work confirmed the need for a correction factor to be included in the proposed modified model. The results revealed that concrete specimens subjected to high temperature and low relative humidity, after the load application, will show higher creep than specimens kept at high temperature and low relative humidity before and after lord application. This indicates that specimens loaded in summer show lower creep than those loaded in winter